Towards universal salt iodisation in India: achievements, challenges and future actions. Issue 4 (18th June 2013) - Rah, Jee H.; Anas, Ansari M.; Chakrabarty, Arijit; Sankar, Rajan; Pandav, Chandrakant S.; Aguayo, Victor M.
Abstract India is one of the first countries to introduce salt iodisation, but the national programme has experienced major setbacks. The purpose of this paper is to review the national efforts towards universal salt iodisation (USI) in India and highlight key challenges in programme implementation. A brief historical overview of the salt iodisation programme is provided and the current status of the household usage of iodised salt and population iodine status is described. The present status of the USI programme together with the challenges being faced towards achieving USI are classified in five categories, which represent the five guiding principles crucial to sustained USI programme success: ensuring political commitment, forming partnerships and coalition, ensuring availability of adequately iodised salt, strengthening the monitoring system and maintaining continuous advocacy, education and communication. A future agenda towards the achievement of USI is also proposed.